EVALUASI PENGGUNAAN TELEMEDISIN PADA PELAYANAN RAWAT JALAN DI RUMAH SAKIT AKADEMIK UGM SAAT PANDEMI COVID-19 DENGAN METODE HOT-FIT - Farhany, Fajrul Falah; Lutfan Lazuardi; Dewi Ratmasari (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2022)
Background: One hospital that has adapted services to the COVID-19 pandemic is the UGM Academic Hospital (RSA UGM). RSA UGM offers long-distance or telemedicine services, later named the Joempa Dokter Telemedicine RSA UGM. Joempa Dokter stands for Journey for Online Electronic Medical Professional Assistance. Telemedicine Joempa Dokter RSA UGM has been running for 1.5 years. Still, it was found that it had not been appropriately utilized by health workers who worked at the Outpatient Installation at RSA UGM. The process flow for telemedicine services was also not adequately systemized, as evidenced by using semi-conventional technology in practice. Objective: To evaluate ‘Joempa Dokter’ telemedicine service at RSA UGM during the COVID-19 pandemic. Methods: The type of research used in this study is a mixed method with an embedded or nested research design using a survey approach and in-depth interviews. This research was conducted in the outpatient ward of RSA UGM from July to August 2022. Results: The flow of telemedicine services for Joempa Dokter RSA UGM starts with patient registration via the Google form, consulting with doctors via the Zoom platform, then prescribing drugs online. Telemedicine services have not been integrated with the SISTEMA RSA UGM, but this service is helpful and easy to use. There are still some deficiencies in this telemedicine service, such as unattractive features; the platform used is still different from registration to postservice; there is no Standard Operating Procedure (SOP) for Joempa Dokter Telemedicine Services; incentives are not appropriate; and telemedicine services are not a priority service at RSA UGM yet. Conclusion: Joempa Dokter Telemedicine at RSA UGM is beneficial as an alternative solution to improve the quality of health services in hospitals during the COVID-19 pandemic. For better service continuity, UGM RSA management needs to prepare Standard Operating Procedures (SPO) and service roadmaps, adjust incentives to improve the performance and motivation of the health workers involved, and service integration with existing information systems at RSA UGM also needs to be done.